Propriedades físico-hídrico-mecânicas do solo e rendimento de milho submetido a diferentes sistemas de manejo - Vieira, Márcio Luis (2006)
The gool of chiseling, which is one of the mechanical practices that can be used on no-tillage (NT) soils, are to reduce bulk density, as well as soil resistance to root penetration, and to increase soil water permeability. The effect of these changes on plant growth and consequently on grain yield depends on climatic conditions; therefore, in soils where soil moisture is ideal, physical limitations tend to be less intense. The present study aims to analyze the changes in the physical, hydraulic, and mechanical properties of an Oxisol, managed under the NT system and chiseled, and the effects of these changes on corn yield. The following soil parameters were assessed: organic carbon (OC) content, texture, consistency, bulk density and particle density, relative density, porosity, water retention curves, mechanical resistance to penetration (RP), least limiting water range (LLWR), water infiltration, and hydraulic conductivity of saturated (K0) and unsaturated soils by means of field tensiometry. Results indicate that chiseled soils hal higher OC content, water infiltration and K0 than NT soils, being therefore an alternative to soil and water conservation, with effects that last for over one year. The critical amplitude and density of LLWR were similar in both management systems. Corn yield was not remarkably different between the management systems. The conclusion is that the effects of chiseling on NT soils can last for two years and may can improve the conditions for soil and water conservation, although improvement or physical and mechanical soil conditions were not be detected by conventional methods